Aplications of Liquid Organic Fertilizer From Agricultural Waste in Wati Plants (Piper methysticum Forst). - Wahida Wahida; Diana Sri Susanti (Faculty of Agriculture, Musamus University, 2018)
Custom reflects the personality and soul of a society or nation, is hereditary and contains belief values ​​in it. The Wati plant (Piper methysticum Forst) is one of the parts or tools used in a Marind tribal in Merauke Regency. As part of custom, it is necessary to develop so that the custom can be maintained. Therefore, most to find simple propagation and cultivation techniques of Wati plants and later can be applied to the community. This study aim to analyze the utilization of agricultural waste into liquid fertilizer which is applied to wati plants. The metode of study with randomized block design (RBD) with five treatments, is P0 (2 l of water) as a control, P1 (10 mL), P2 (20 mL), P3 (30 mL), and P4 (40 mL). Each treatment was repeated as many as five times, so that 25 experimental units. The parameters observed were the content of N, K, and P2O5, from agricultural waste, stem diameter, number of leaves and stem length. The results showed that the N and P2O5 contents were low, whereas K had met the minimum technical requirements for POC. The results of the POC application showed that the best growth of wati plant seeds for plant height and number of leaves with a dose of 40 mL/L water.